Elective caesarean section at 38 weeks versus 39 weeks: neonatal and maternal outcomes in a randomised controlled trial1. Issue 9 (20th May 2013) - Glavind, J; Kindberg, SF; Uldbjerg, N; Khalil, M; Møller, AM; Mortensen, BB; Rasmussen, OB; Christensen, JT; Jørgensen, JS; Henriksen, TB
<x xml:space="preserve">Abstract</x> Objectives To investigate whether elective caesarean section before 39 completed weeks of gestation increases the risk of adverse neonatal or maternal outcomes. Design Randomised controlled multicentre open‐label trial. Setting Seven Danish tertiary hospitals from March 2009 to June 2011. Population Women with uncomplicated pregnancies, a single fetus, and a date of delivery estimated by ultrasound scheduled for delivery by elective caesarean section. Methods Perinatal outcomes after elective caesarean section scheduled at a gestational age of 38 weeks and 3 days versus 39 weeks and 3 days (in both groups ±2 days). Main outcome measures The primary outcome was neonatal intensive care unit (NICU) admission within 48 hours of birth. Secondary outcomes were neonatal depression, NICU admission within 7 days, NICU length of stay, neonatal treatment, and maternal surgical or postpartum adverse events. Results Among women scheduled for elective caesarean section at 38+3 weeks 88/635 neonates (13.9%) were admitted to the NICU, whereas in the 39+3 weeks group 76/637 neonates (11.9%) were admitted (relative risk [RR] 0.86, 95% confidence interval [95% CI] 0.65–1.15). Neonatal treatment with continuous oxygen for more than 1 day (RR 0.31; 95% CI 0.10–0.94) and maternal bleeding of more than 500 ml (RR 0.79; 95% CI 0.63–0.99) were less frequent in the 39 weeks group, but these findings were insignificant after adjustment for multiple comparisons. The risk of adverse neonatal or maternal outcomes, or a maternal composite outcome (RR 1.1; 95% CI 0.79–1.53) was similar in the two intervention groups. Conclusions This study found no significant reduction in neonatal admission rate after ECS scheduled at 39 weeks compared with 38 weeks of gestation.